Perception Of Service Quality, Value, And Satisfaction In Determining Customer Loyalty: A Study In 5-Star Hotels In Penang - Lim, Ee Hui (2004)

(untitled)
Kepuasan pelanggan senng dianggapkan sebagai penentuan utama dalam penyelidikan tentang kesetiaan pelanggan. Bagaimanapun, bukti empirikal mengenai hubungan antara kesetiaan dan kepuasan pelanggan masih kabur. Dalam penyelikan ini kesetiaan pelanggan diaplikasikan dalam sektor. perkhidmatan dengan menggunakan model ACSI (American Customer Satisfaction Index). Salah satu sumbangan kepada struktur persamaan model ini ialah penyelipan persepsi nilai sebagai satu faktor sampingan dalam penentuan kesetiaan pelanggan. In research on customer loyalty in services, satisfaction has often been mentioned as an important determinant. However, empirical evidence concerning the relationship between loyalty and satisfaction has remained unclear. This research develops a general service sector of customer loyalty from the model of ACSI (American Customer Satisfaction Index). A key contribution to the structural equation model is the incorporation of perception of value into an integrated of customer loyalty.